ANALYSIS OF THE PRINCIPAL'S ROLE IN THE IMPLEMENTATION OF SCHOOL-BASED MANAGEMENT AT STATE ELEMENTARY SCHOOL 3 PANJI - Damayanti, Ni Made Nia Putri; Darmayanti, Ni Luh Komang Ayu Sukma Intan; Widiasari, Ketut; Diantara, I Komang Arya; Werang, Basilius Raden (Journal of Finance, Economics and Business, 2025)
This study aims to analyze the role of principal leadership in the implementation of School-Based Management (SBM) at SD Negeri 3 Panji. The results indicate that the principal applies a participatory approach involving teachers, staff, and the school committee in decision-making, thereby creating a sense of ownership and shared responsibility. The principal's ability to inspire and motivate the team contributes to the creation of a clear shared vision that supports innovation and creativity. Despite challenges such as miscommunication and excessive workload, the principal demonstrates an adaptive and proactive attitude in addressing these obstacles. This study concludes that inclusive and collaborative leadership is crucial in creating a school environment that is responsive to educational needs and enhances the quality of learning.